Translanguaging and Social Justice: The Stance of the Minority Languages through the Lens of the Lesotho Curriculum Policy - Malisema Francina Makoa; Kananelo Sylvester Moea (E-Journal of Humanities, Arts and Social Sciences, 2025)
Translanguaging refers to both the discourse practices of bilinguals, as well as to pedagogical practices that use the entire linguistic repertoire of bilingual students flexibly in order to teach rigorous content and develop language practices for academic use. Translanguaging can be used as an effective tool in the teaching of all subjects in the classroom of students of different languages. This study sought to assess the stance of the minority languages through the lens of the Lesotho curriculum policy focusing on Translanguaging and social justice. The study engaged a qualitative research method where the issue of translanguaging will be explained using words. Based on the findings of this study, it was discovered that the policy recognises only Sesotho and English as languages of instruction and official languages. Also, it was found that the policy is very silent about roles that can be played by minority languages thus disregarding them even though it appears to be supporting them. Thus, it is concluded that the Lesotho allows social inequality and no translanguaging thus a problem for the education and learning of the minority language speakers. It recommends that translanguaging be used in all grades in all subjects because this will help students understand complex concepts. Moreover, Sesotho should not be used as the only language when code-switching from English to other languages. This study contributes more insight into the development and review of CAP for incorporation of minority languages.